Development of Parasitemia and anemia caused by T. Orientalis infection in experimental calves (Mongolian Journal of Agricultural Sciences, 2018)
In the present study, we have studied development of parasitemia and anemia which caused by T. orientalis infection in experimental calves using different kind of laboratory tests such us blood smear test, blood cell examination test  and conventional PCR. The blood smear test is still one of easiest, effective diagnostic methods. According to our results the sensitivity of this test was as same as PCR.